INFLUENCE OF MANAGEMENT SYSTEMS ON SOIL PHYSICAL ATTRIBUTES (Nucleus, 2023)
The deterioration of soil quality has been widely studied and debated in Soil Science. Thus, this work aims to evaluate the effect of soil management systems, regarding the soil physical attributes. A New Holland tractor was used, model TL75, 4 x 2 TDA, in a randomized block design, with a split-plot plot scheme (5 x 3), that is, five soil tillage methods (leveling harrow, rotary hoe, manual weeding, subsoiler, and disc plow) and three periods (before tillage, after tillage and at the end of the implanted crop cycle) with three replicates, totaling 45 experimental units. For the water retention curve (SWRC), the SWRC Fit program was used. No significant difference was found among the soil tillage methods, however, when comparing the time before and after the preparation and the end of the implanted crop cycle, changes in the physical properties of the soil were observed in both treatments. The evaluation of the different methods allowed us to observe that the closer the results of parameters R² and the AIC, the most satisfactory the SWRC. Therefore, it is concluded that the different treatments do not cause changes in the physical properties of the soil, but when working with soil collections before and after sowing and harvesting, changes are found in the soil profile. The SWRC assessment methods were satisfactory; however, the Kosugi and Fredlund and Xing methods did not present significant values when compared with the others.